Power and conflict in organizations / edited by Robert L. Kahn and Elise Boulding - "Kahn , Robert .L.(ed.)"; Kahn, Robert L.(Ed.) (New York, 1964)
THE MATERIALS IN THIS BOOK WERE ORIGINALLY discussed at two seminars conducted by the Foundation for Research on Human Behavior. The first of these seminars, held in February, 1960, dealt with research on power in organizations. The second, held in October, 1961, in cooperation with the Cen- ter for Research on Conflict Resolution, was devoted to studies of conflict in organizations. At the seminar on power in organizations, a group of social scientists made presentations ranging from reports of research from small-group and laboratory experiments to field studies in organizations and to broader studies of power in society. These social scientists included John R. P. French, Jr., Robert L. Kahn, and Abraham Kaplan. The seminar was planned by Hollis W. Peter, then associate director of the Foundation, and chaired by Samuel P. Hayes, then director. Similarly, in the second seminar, theoretical advances and new research findings on conflict were discussed. Presentations were by another group of social scientists, including Kenneth Boulding, Robert L. Kahn, Daniel Katz, R. Nevitt Sanford, Her- bert Shepard, and Donald Wolfe. This seminar was planned by Sven Lundstedt, then associate director of the Foundation, with Hollis Peter, then director, who also chaired the meeting. At each of the seminars, an active group of business par-ticipants took part in the discussion and suggestions for application which are reported in this book.
Keywords: Social control